Spectroscopic measurements of atmospheric N2O at Syowa Station, Antarctica (abstract) - Makino, Yukio; Muramatsu, Hisafumi; Kawaguchi, Sadao; Yamanouchi, Takashi; Tanaka, Masayuki; Ogawa, Toshihiro (1986)
P(論文) departmental bulletin paper